Amitav ghoshs Sea of poppies (2008): a web of gender, cultural and mythic relations in the nineteenth-century colonial India - Ramos, Regiane Corrêa de Oliveira (2016)
This doctoral dissertation focuses on Amitav Ghoshs Sea of Poppies (2008) to investigate, from a postcolonial perspective, the way in which the writer deconstructs gender in the nineteenth-century India. In Chapter I, I analyze men and women within the Indian familial space in the nineteenth century, demonstrating how both are subjected to the disempowering effects of traditional rituals (such as sati), structures of Brahminical morality and patriarchal violence. The main character pair Deeti and Kalua is an example of how the persons are sexually assaulted (rape) and then silenced by an oppressive system. Chapter II, I examine men and women within the British colonial space, indicating how they are effected by the opium cultivation in the Indian hinterland. The peripheral characters peasants, eurasian and convicts are highlighted to show how they are uprooted from homeland and forced to be taken across the seas by the colonial administration to work as indentured labour. In Chapter III, I investigate the gender roles ascribed to Indians by the British colonizers. The secondary character pair Nob Kissin and Taramony shows how Ghosh deconstructs gender with the use of Indian mythology and storytelling. In the conclusion, I point out how Indian mythology is retrieved as an instrument of resistance.